Assisted Jumping in Healthy Older Adults: Optimizing High-Velocity Training Prescription - Tufano, James J; Vetrovsky, Tomas; Stastny, Petr; Steffl, Michal; Malecek, Jan; Omcirk, Dan (Journal of strength and conditioning research, 2022)
ABSTRACT: Tufano, JJ, Vetrovsky, T, Stastny, P, Steffl, M, Malecek, J, and Omcirk, D. Assisted jumping in healthy older adults: optimizing high-velocity training prescription. J Strength Cond Res 36(6): 1518-1523, 2022-Because older adults benefit from power training, training strategies for athletes such as supramaximal velocity-assisted jumping could also be useful for older adults. However, optimizing-assisted exercise prescription in older adults remains uninvestigated. Therefore, the purpose of this study was to determine the effects of different bodyweight (BW) assistance levels on jumping force and velocity in healthy older adults. Twenty-three healthy older adults (67.6 ± 7.6 years, 167.0 ± 8.8 cm, 72.7 ± 14.3 kg, and 27.1 ± 6.9% body fat) performed 5 individual countermovement jumps at BW, 90, 80, 70, and 60% of BW. Jumps were performed on a force plate, which provided peak take-off force (TOF), flight time, and peak impact force. A linear position transducer measured peak concentric velocity (PV). The rating of perceived exertion (RPE) was also assessed after each condition. Take-off force was greater during BW than all other conditions, 90 and 80% were greater than 70 and 60%, but there were no differences between 80 and 90% or between 70 and 60%. The FT progressively increased at all assistance levels, and PV was faster for all assistance levels than BW, with no differences between assistance levels. Impact force was greater during BW than 80, 70, and 60% and was greater during 90% than 60%. The RPE was less than BW during all assistance conditions but was the least during 70%. Implementing assisted jumping between 70 and 80% of BW in older adults likely provides the ideal combination of force, velocity, and RPE.
Keywords: svalová síla; Health Status; Prescriptions; zdravotní stav; lidé; Aged; Muscle Strength; sportovci; tělesná hmotnost; lékařské předpisy; Humans; Athletes; Body Weight; senioři